Thiol redox chemistry: role of protein cysteine oxidation and altered redox homeostasis in allergic inflammation and asthma - Hoffman, SM (J Cell Biochem, 2015)
Asthma is a pulmonary disorder, with an estimated 300 million people affected worldwide. While it is thought that endogenous reactive oxygen species (ROS) and reactive nitrogen species (RNS) such as hydrogen peroxide and nitric oxide, are important mediators of natural physiological processes, inflammatory cells recruited to the asthmatic airways have an exceptional capacity for producing a variety of highly reactive ROS and RNS believed to contribute to tissue damage and chronic airways inflammation. Antioxidant defense systems form a tightly regulated network that maintains the redox environment of the intra- as well as extracellular environment. Evidence for an oxidant-antioxidant imbalance in asthmatic airways is demonstrated in a number of studies, revealing decreased total antioxidant capacity as well as lower levels of individual antioxidants. Thiols in the form of GSH and sulfhydryl groups of proteins are among the most susceptible oxidant-sensitive targets, and hence, studies investigating protein thiol redox modifications in biology and disease have emerged. This perspective offers an overview of the combined efforts aimed at the elucidation of mechanisms whereby cysteine oxidations contribute to chronic inflammation and asthma, as well as insights into potential cysteine thiol-based therapeutic strategies.